Manghobasi dalam Batak Toba sebagai Ekspresi Kasih dan Persekutuan dalam Gereja Katolik: Studi Fenomenologis - Ona Sastri Lumban Tobing; Exnasia Retno Palupi Handayani; Florentina Dwi Astuti; Oktavianey Gasperius Patana Hamahena Meman (Borneo Review, 2025)
The manghobasi tradition in Batak Toba culture represents a form of communal solidarity and mutual assistance deeply rooted in social life. Within the context of Batak Toba Catholic communities, manghobasi is not merely a social act but also an expression of love and ecclesial communion grounded in the teachings of Christ. This study aims to explore the meaning of manghobasi among Batak Toba Catholics and to identify the theological values embodied in this practice. The research employs a qualitative phenomenological approach, focusing on the lived experiences of Catholic believers who practice manghobasi. Data were collected through in-depth interviews and Questionnaire, then analyzed using data reduction, meaning categorization, and thematic description. The findings reveal that manghobasi encompasses three essential meanings: (1) as a manifestation of God’s love through selfless service to others; (2) as an expression of ecclesial communion, strengthening solidarity and togetherness within the community; and (3) as a form of inculturated Catholic faith in Batak Toba culture, where Gospel values are embodied in local tradition. Thus, manghobasi bridges faith and culture, serving as a pastoral inspiration for the Church to nurture love and solidarity among the faithful.